Peran Marketing dalam Media Sosial untuk Membantu Pemasaran UMKM di Masa Pandemic Covid-19 - Amanda Amanda (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the role of marketing in social media to help MSMEs marketing during the Covid-19 Pandemic. The research method used in this study is descriptive qualitative with data collection techniques, namely interviews. The results of the study show that the role of marketing in social media to help marketing MSMEs during the Covid-19 pandemic greatly helped the household economy. By utilizing social media marketing, these business actors use various social media platforms as storefronts to promote the products and services they offer. Keywords: Social Media Marketing, Social Media